Long-term results of surgically assisted maxillary protraction vs regular facemask - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2014)
Objective: To evaluate the short- and long-term treatment results of rapid maxillary expansion (RME) and surgical assistance during maxillary protraction with a facemask (FM). Materials and Methods: This study was carried out in 28 patients (12 male, 16 female) with maxillary retrognathisnn, anterior crossbite, and Class III skeletal and dental malocclusion characteristics. Seventeen patients (9 male, 8 female) with mild maxillary retrognathism were treated by RME and FM. The other 11 patients (8 female, 3 male), who had moderate to severe maxillary retrognathism, were treated with surgically assisted FM treatment. Patients treated with RME and FM were recalled after 5.64 years, and the surgically assisted FM group was recalled after 6.08 years. Cephalometric films taken before treatment (T-0), right after maxillary protraction (T-1), and at recall (T-2) were used to evaluate and compare the results. Results: In the short term, good maxillary advancement and a shorter treatment period were achieved with surgically assisted FM therapy. However, in the long term, maxillary advancement and some soft tissue improvements were lost. On the other hand, in the RME and FM protraction group, maxillary advancement and soft tissue improvement were well maintained. Conclusion: In the short term, statistically significant maxillary advancement was achieved with surgically assisted maxillary protraction. However, in the long term, these sagittal changes were not stable, whereas RME and FM provided stability.
Keywords: Corticotomy; Facemask; Long-term; Class III; Stability; RIGID EXTERNAL DISTRACTION; CLEFT-LIP; SKELETAL STABILITY; OSTEOGENESIS; EXPANSION; ADVANCEMENT; THERAPY; PALATE; CHILDREN; DEVICE